ЕМОТИВНО-ОЦІННІ ВИМІРИ ОНІМНОГО ПРОСТОРУ В МОВОТВОРЧОСТІ ОЛЕКСАНДРА ДОВЖЕНКА (World Science, 2020)
The article deals with theoretical problems of onomastics. The study was aimed to consider the development of linguistic science in diachrony. The difference between artistic and linguistic onomastics has been identified. The status of the onyms in the context of the artistic works has been determined. The part of the study was devoted to clarifying the tangential relations of onomastics with related disciplines. Theoretical and practical achievements in the field of onymia were analyzed. An attempt to structure the classification and description of all components of the onomatology filling in Alexander Dovzhenko`s idiolect was made. It was revealed that the most used group of onyms are toponyms and anthroponyms with emotional and evaluative meanings.